2012
DOI: 10.1136/bcr.11.2011.5145
|View full text |Cite
|
Sign up to set email alerts
|

A rare ophthalmic presentation of pituitary metastases

Abstract: BACKGROUNDPituitary metastases are very rare and the most common clinical presentation with a pituitary metastasis is diabetes insipidus, which may be the fi rst manifestation of the underlying tumour. We present a case who presented with an ophthalmoplegia, headache and reduced vision and later on diagnosed with pituitary metastases. CASE PRESENTATIONAn 83-year-old woman presented to the eye casualty department with a history of progressive horizontal diplopia, fronto-occipital headache and reduced vision in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…The frequencies of primary sites are summarized in Fig. 1 (10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 10...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequencies of primary sites are summarized in Fig. 1 (10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, 100, 101, 10...…”
Section: Resultsmentioning
confidence: 99%
“…In the City of Hope series contained herein, breast cancer and lymphoma were equally the most common primary metastasis source. It is hypothesized that elevated hormone levels in the pituitary gland, especially prolactin, may attract metastatic cells (85). Recent studies have found that anti-HER-2 treatment can facilitate Pit Met (145, 146, 147).…”
Section: Discussionmentioning
confidence: 99%
“…At least in part the reason is that these two types of malignancies are most commonly encountered in clinical practice. Less often described are metastasis of renal cell carcinoma, gastrointestinal tumours, lymphomas, leukemias, thyroid carcinomas, myeloma, hepatocellular carcinoma and rhabdomyosarcoma (Table 1) [1,2,[7][8][9][10][11][12][13][14][15][16][17][18][19]. When confirming the metastasis in the pituitary, there are frequently metastases present at several other locations, most often in bones.…”
Section: Discussionmentioning
confidence: 99%